The biopolitical production of tourism areas in Lesotho: the case of Bokong Nature Reserve - Itumeleng Mokhele (Via@)
Tourism cuts across all forms of human interaction being their living space, frontiers, socio-economic and cultural aspects. The paper seeks to establish the impact of tourism development on local communities and to assess the effects of biopolitical production of a tourism area at Bokong Nature Reserve in Lesotho. The study is qualitative in nature. Narrative inquiry and in-depth interviews were used to collect data from one village at Ha Lejone, in the Leribe district. Results show that the construction of the tourist site occupies the community land which was used for various purposes. Livestock is captured by the nature reserve management while the traditional school that was located on the site stripped for tourism development was demolished. However, the content analysis of the narrative depicts a little ray of positivity as the narrator states that local communities were trained in making fire belt. It is concluded that tourism as a biopolitical phenomenon deprive local communities of the biological and the environmental endowments that once belonged to them.